EFL Students’ Perceptions on the Use of Storytelling towards English Speaking Proficiency - Budiarti Budiarti; Juhansar Juhansar; Dyah Ayu Rahmawati; Kikin Feby Alamsyah; Angella Muna Mawar; Suryo Sudiro (Universitas Muhammadiyah Enrekang, 2022)
In this modern era, where everything is entirely technological, storytelling can still be found everywhere, not only in children's reading books or school books but also on the internet, for learning media. In Indonesia itself, there are a plethora of storytellings. Storytelling as a medium for teaching speaking is also expected to improve EFL students' language skills. Using storytelling as a method to teach speaking is also one of the ways that teaching speaking activity becomes enjoyable. In this study, the research aims to know EFL students’ perception of storytelling and their proficiency in English speaking skills using storytelling. This research is conducted using a quantitative method. The data are collected by questionnaire to determine their understanding of storytelling and test; the scoring method employs a speech to text application; we grade three aspects: pronunciation, fluency, and accuracy. The sample of this research is UTY English education EFL students in 2020 and 2021. This research shows that using storytelling can improve EFL students speaking skills. Storytelling to teach speaking to EFL students is hoped that EFL students will be able to hone their speaking skills consciously and use storytelling strategies. In this study, it is known that storytelling is possible to teach speaking skills in the classroom.